Detection of Paracoccidioides spp. in environmental aerosol samples - Arantes, Thales Domingos; Theodoro, Raquel Cordeiro; Macoris, Severino Assis da Graça; Bagagli, Eduardo (Oxford University Press (OUP), 2013)
Taking into account that paracoccidioidomycosis infection occurs by inhalation of the asexual conidia produced by Paracoccidioides spp. in its saprobic phase, this work presents the collection of aerosol samples as an option for environmental detection of this pathogen, by positioning a cyclonic air sampler at the entrance of armadillo burrows. Methods included direct culture, extinction technique culture and Nested PCR of the rRNA coding sequence, comprising the ITS1-5.8S-ITS2 region. In addition, we evaluated one armadillo (Dasypus novemcinctus) as a positive control for the studied area. Although the pathogen could not be isolated by the culturing strategies, the aerosol sampling associated with molecular detection through Nested PCR proved the best method for discovering Paracoccidioides spp. in the environment. Most of the ITS sequences obtained in this investigation proved to be highly similar with the homologous sequences of Paracoccidioides lutzii from the GenBank database, suggesting that this Paracoccidioides species may not be exclusive to mid-western Brazil as proposed so far. © 2013 ISHAM.
Keywords: Cyclone sampler; Ecology; Environmental samples; Paracoccidioides brasiliensis; Paracoccidioidomycosis; aerosol; air pollution; Brazil; fungal detection; fungal gene; gene sequence; molecular diagnosis; nonhuman; nucleotide sequence; Paracoccidioides; Paracoccidioides lutzii; polymerase chain reaction; sequence homology; Aerosols; Air Microbiology; Animals; Armadillos; Base Sequence; Cricetinae; DNA, Fungal; DNA, Ribosomal; DNA, Ribosomal Spacer; Environment; Environmental Monitoring; Mesocricetus; Molecular Sequence Data; Molecular Typing; Mycological Typing Techniques; Phylogeny; Polymerase Chain Reaction; Polymorphism, Genetic; Sequence Analysis, DNA; Soil Microbiology; Spores, Fungal; Armadillo; Dasypus novemcinctus